(3JJeI QhM GdQhMs - (3YjSi Hf dWa Gddgs
(3ChdgG (B:s
(3hHYO aEfgG deG cGfJ haGI ehdGfG GdefUhQ HGddg GdbGSe Hf eMeO cGf CeQkG YXjekG s
(3BNQgG (B:s
(3ajfG ONd Edi UfYGA ehdGfG eMeO Hf GdMSjf aGSJbQ ai OGQ GdeOQSI GdTQbjI hGdMeO ddg QH GdYGdejf JeJ gPg JJeI JGQjN QhM GdQhM s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3PgHJ HYV GdcdeGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs